BK virus nephropathy in kidney transplantation (literature review - S. V. Popov; R. G. Huseynov; K. V. Sivak; I. N. Isakova-Sivak; V. V. Perepelitsa; T. A. Lelyavina (Вестник трансплантологии и искусственных органов)
The article presents a review of the literature on the current problem of modern transplantology – BK viral nephropathy after nephrotransplantation. Risk factors for BK virus reactivation in immunocompromised patients are reflected. The issues of screening and diagnosis of BK viral infection in people with a transplanted kidney are considered. The role of BK viral nephropathy in renal graft loss is emphasized. The clinical manifestations and treatment strategies of BK viral nephropathy in kidney transplantation are discussed.